(untitled) (African Multidisciplinary Journal of Research, 2022)
Management of community utilization of protected resources in protected forests is a huge challenge, particularly in the Mount Kenya region because of limited research data on the dynamics and characteristics of households living adjacent to protected forests. This research, conducted in the Mount Kenya West protected forest, sought to examine household perceptions on the different sources of pasture and fodder, to assess the significant household characteristics in driving smallholder farmers dependence on protected forests for pasture and to assess the significance of household characteristics in driving smallholder farmers’ dependence on protected forests for grass harvesting for livestock fodder. The research followed a cross-sectional research design with smallholder farmers dwelling adjacent to three forest blocks, namely, Kahurura, Hombe, and Chehe as the target population. The data was collected from May to October 2019. Questionnaires were used to collect data from a sample of 453 participants. Multiple logistic regression was used to assess the significant household characteristics in driving forest dependence cattle grazing and grass harvesting. Results obtained revealed that significant household characteristics driving forest dependence for pasture were the ownership of zero-grazing unit (p=0.03 < 0.05), the proportion of cattle under zero grazing (p=0.04 < 0.05) and proximity to the forest (p=0.08 <0.1). The proportion of cattle in zero-grazing units had the highest marginal effect, followed by ownership of zero-grazing units with proximity to the forest having the lowest marginal effects. Significant household characteristics driving smallholder famers’ dependence on protected forests for grass harvesting for cattle included: a household’s socio-economic status (p=0.06<0.1), a household’s total size of land owned (p= 0.02 < 0.05), and proportion of cattle kept under a zero-grazing unit (p=0.07<0.1). The proportion of cattle in zero-grazing unit had the highest marginal effects followed by the total size of land owned. These findings contribute to knowledge on the significant micro-level characteristics driving the two forms of forest dependence investigated. Future studies are needed to explore the meso-and- macro-level factors that interact with household characteristics identified to drive forest dependence for livestock grazing and grass harvesting. Keywords: Forest dependency; Local communities; Logistic regression, Livestock, Livelihoods, Mount Kenya West protected forest